Multiplex polymerase chain reaction detection of Shiga toxin genes and antibiotic sensitivity of Escherichia coli O157:H7 isolated from beef meat in Quetta, Pakistan. Issue 6 (4th September 2018) - Samad, Abdul; Abbas, Ferhat; Ahmad, Zafar; Tanveer, Zunera; Ahmad, Irshad; Patching, Simon G.; Nawaz, Nighat; Asmat, Muhammad Tauseef; Raziq, Abdul; Asadullah; Naeem, Muhammad; Akhtar, Muhammad Aleem; et al.
Abstract: The objective of this study was to conduct a qualitative analysis of raw beef meat sold in the city of Quetta, Pakistan for presence and drug sensitivity of the potentially pathogenic Escherichia coli strain O157:H7. The study used 200 raw beef meat samples collected from retail butcher shops. Conventional and rapid biochemical tests, latex agglutination and multiplex polymerase chain reaction (PCR) using primers designed for the rfb O157 and flic H7 genes were used to detect E. coli O157:H7. All O157:H7 isolates were also tested for Shiga toxin genes stx 1 and stx 2 . The prevalence of E. coli O157:H7 in collected beef meat samples was 10%. Detection through PCR was found more sensitive than detection of O and H antigens. The quantity of E. coli O157:H7 isolates positive for Shiga toxins was 50% (20% for stx 1, 45% for stx 2 and 10% for both stx 1 and stx 2 ). Season wise variation showed highest E. coli O157:H7 prevalence during summer months. A further concern is that E. coli O157:H7 isolates were resistant to a range of common antibiotics. The results indicate an urgent need for applying proper food hygiene practices in the Quetta region to reduce incidence of foodborne diseases and they also emphasize the global problem of antimicrobial resistance. Practical applications: E. coli O157:H7 is as a potentially threatening foodborne pathogen. A significant prevalence of E. coli O157:H7 detected in raw beef meat from retail outlets in the city of Quetta indicates an urgent need for applying proper food hygiene practices in the Quetta region to reduce the incidence of foodborne diseases. Furthermore, resistance of the E. coli O157:H7 isolates to a range of commonly used antibiotics emphasizes the global problem of antimicrobial resistance. The multiplex PCR method used here is a reliable, sensitive, and relatively rapid technique for detecting E. coli O157:H7 in food and environmental samples and important for ongoing surveillance to minimize contamination of raw meat products and associated cross contamination by E. coli O157:H7.